Consumer Trust in the Digital Environment - López Jiménez, David; Dittmar, Eduardo Carlos; Vargas Portillo, Jenny Patricia (Law, State and Telecommunications Review, 2022)
[Purpose] The objective of this paper is to study alternative dispute resolution mechanisms in both the electronic contracting of goods and/or services and interactive advertising. [Methodology/Approach/Design] The Spanish and European regulations will be analyzed in terms of regulation and self-regulation mechanisms. Self-regulation instruments are a suitable complement to current legal regulations. [Findings] Although disputes that may arise between consumers and businesses can be settled in court, the circumstances of cases involving e-commerce and interactive advertising may determine that the use of out-of-court instruments is appropriate. In this sense, self-regulation systems promote conflict prevention. In the event that it arises, it is about reaching a faster resolution than the courts of justice, cheaper and carried out by specialists in the matter. [Practical Implications] The implications of this investigation may be applicable to transactions of goods and services in general, to civil society and to the public sector. [Originality] This investigation demonstrates the convenience and significance of considering out-of-court dispute resolution mechanisms over conventional means, both in Spain and in the European Union. The self-regulation instruments are based on a Code of Conduct and an impartial and independent control body that applies it. Normally, codes of conduct are based on the application of different instruments for extrajudicial conflict resolution.